Association Between Various Types or Statuses of Smoking and Subjective Cognitive Decline Based on a Community Health Survey of Korean Adults - Kim, Ji Hee; Chang, In Bok; Kim, Yoo Hwan; Min, Chan Yang; Yoo, Dae Myoung; Choi, Hyo Geun (Frontiers in Neurology, 2022)
Objectives The relationship between smoking and subjective cognitive decline (SCD), which is defined as the subjective perception of cognitive decline, is not well known. This study aimed to investigate the relationship of various types of smoking, including E-cigarette smoking and the use of E-liquid, with the incidence of SCD among Korean adults. Methods We evaluated the 2018 Korean Community Health Survey data collected from community-dwelling people in Korea. A total of 104,453 non-smokers, 38,607 past smokers, and 26,776 current smokers with eligible data were included in the study. SCD was assessed using the Behavioral Risk Factor Surveillance System. The past or current smoking pack-years throughout each participant's entire life were calculated. Multiple regression analyses were carried out to estimate the adjusted odds ratios (ORs) as measures of the association between each type of smoking and SCD after adjustment for potential confounders. Results Compared to no exposure, passive smoking was associated with higher odds of SCD. Compared to non-smokers, past smokers had a higher OR for SCD; however, current smokers did not. There were no significant associations between passive smoking and SCD in the non-smoker and past smoker groups, but there was a significant relationship between them in the current smoker group. While the cumulative dose of smoking was correlated with an increased OR of SCD in each group of current smokers and past smokers, E-cigarette smoking and the use of E-liquid were not associated with higher ORs in the current smoker group. Conclusion Our findings support that passive smoking and past smoking are significantly associated with SCD and that more cumulative exposure to smoking is correlated with a higher OR of SCD.